Gender-sensitive health service framework for women prisoners in Thailand: A qualitative study - Kumtanat, Threenush; Rungreangkulkij, Somporn (Belitung Nursing Journal, 2026)
Background: Prison health is increasingly recognized as part of community health, especially as the population of incarcerated women grows and presents unique health needs. Yet, evidence on how Thailand’s prison health system addresses gender sensitivity, particularly when viewed through the WHO’s Six Building Blocks framework, remains limited. This system-level knowledge gap restricts efforts to improve equitable care for women prisoners. Objective: This study explored health service delivery for women prisoners in Northeastern Thailand from September 2022 to August 2024 through the WHO’s Six Building Blocks framework, identifying barriers, enablers, and policy implications for gender-sensitive prison healthcare. Methods: A qualitative descriptive design was employed. Data were collected through participatory and non-participatory observations, in-depth interviews, and document reviews with 35 informants, and analyzed using the WHO Health System Framework. Trustworthiness was ensured by triangulation, member checking, and prolonged engagement. Results: The healthcare system encompassed all six WHO building blocks: service delivery, health workforce, health information, access to medicines and technologies, financing, and governance. However, gaps persisted in gender-sensitive services such as gynecological and trauma-informed care, nurse workload, and budget allocation. Initiatives such as telemedicine and the Pansuk Project provided support but were insufficient to address women’s specific vulnerabilities. Conclusion: While structural improvements have been achieved, strengthening gender-sensitive care is necessary. Nurses should integrate trauma-informed and gynecological competencies, supported by better shift management and telemedicine systems. Policy measures, including gender-responsive budgeting and inter-ministerial collaboration, are crucial to the sustainable integration of prison health into national public health.